Developing the Capacity to Support Beginning Teachers in Wales: Lessons Learnt from the Masters in Educational Practice. (1st March 2017) - Hadfield, Mark; Connolly, Mark; Barnes, Yvonne; Snook, James
One of the key requirements for any system level reform to be effective is to ensure that 'at the point of delivery' the necessary capacity is available to those responsible for its implementation (Mourshed et al., 2010; Robinson et al., 2011). The Masters in Educational Practice (MEP) was a key element of the Welsh Government's strategy for professional development and school improvement. The paper does not seek to evaluate the MEP programme's effectiveness (forthcoming) but, instead, considers its design and 'enactment' (Ball et al., 2012). The paper approached the issues of the enactment of the MEP: how the programme was shaped by the interaction of individual and collective agency in overlapping contexts, from the theoretical perspective of capacity building at a system level (Hadfield and Chapman, 2009). The analytical focus of the paper is on the nature of the temporary intermediate organisation (Asheim, 2002) constructed to lead the implementation of the MEP and the challenges it faced in accessing, cohering and aligning sufficient capacity from within, and external to, the Welsh education system.